2012
DOI: 10.1189/jlb.1211641
|View full text |Cite
|
Sign up to set email alerts
|

BTLA expression contributes to septic morbidity and mortality by inducing innate inflammatory cell dysfunction

Abstract: A proper innate inflammatory response is essential for prevention of the systemic inflammation associated with sepsis. BTLA is an immune-regulatory receptor demonstrated to be expressed not only on adaptive immune populations and have potent inhibitory effects on CD4(+) T cells but is also expressed on innate cell populations (CD11c(+) and CD11b(+) cells) and has been shown to diminish pathogen clearance following bacterial and parasite infection. The role of BTLA in sepsis and the mechanisms by which BTLA alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 38 publications
9
100
1
Order By: Relevance
“…Sun et al (18) have shown that BTLA −/− mice exhibit significantly higher bacterial clearance compared with WT mice in the early phase of bacterial infection. Shubin et al (19) have also shown that BTLA −/− mice exhibited a higher rate of survival and protection from cecal ligation and puncture. Moreover, Adler et al (20) have shown that BTLA −/− mice exhibit strongly enhanced parasite clearance and that the increased clearance is seen before the onset of acquired immune responses.…”
Section: B and T Lymphocyte Attenuator Inhibits Lps-inducedmentioning
confidence: 97%
See 1 more Smart Citation
“…Sun et al (18) have shown that BTLA −/− mice exhibit significantly higher bacterial clearance compared with WT mice in the early phase of bacterial infection. Shubin et al (19) have also shown that BTLA −/− mice exhibited a higher rate of survival and protection from cecal ligation and puncture. Moreover, Adler et al (20) have shown that BTLA −/− mice exhibit strongly enhanced parasite clearance and that the increased clearance is seen before the onset of acquired immune responses.…”
Section: B and T Lymphocyte Attenuator Inhibits Lps-inducedmentioning
confidence: 97%
“…Because BTLA −/− mice have been reported to exhibit significantly higher pathogen clearance compared with WT mice (18)(19)(20), the administration of 6A6 is of potential concern for the suppression of pathogen clearance. However, it has been reported that 6A6 does not perturb protective immunity against pathogens (16,24).…”
Section: Discussionmentioning
confidence: 99%
“…A phase Ib/IIa study testing a PDL1-specific antibody in patients with sepsis is under way, and secondary outcome measures in this trial include changes in biomarkers of immune suppression as readouts of the effects of treatment 126 . Other immune checkpoints that have been targeted in preclinical sepsis models and have been shown to improve survival include B and T lymphocyte attenuator (BTLA), and cytotoxic T lymphocyte-associated molecule 4 (CTLA4) 127,128 , but studies investigating the targeting of these checkpoints in human sepsis have not yet been performed.…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…During acute experimental sepsis, HVEM-BTLA interactions on innate populations worsen outcomes with respect to organ injury, bacterial burden, and mortality (106) HVEM and adaptive immune responses. Helper Th1 CD4 ϩ T cells are considered to represent the major immunopathologic cell type in HSK (9,10,15).…”
Section: Hvem Alters Host Immune Responses To Hsvmentioning
confidence: 99%